Household and occupational air pollution, and demographic drivers of COPD: a hospital-based cross-sectional study in a high-pollution urban setting - Amrendra Kumar Singh; Ashutosh Kumar Pathak; Gaurav Saini (Journal of Environmental Health Science and Engineering, 2026)

Overlooked Health Risks in Rural Settings: PM2.5 Exposure and Concomitant Premature Mortality and Economic Burden Assessment in Punjab and Haryana, India - Amrendra Kumar Singh; Ashutosh Kumar Pathak; Gaurav Saini (Water, Air, & Soil Pollution, 2026)

Metabolic engineering of lipids for crop resilience and nutritional improvements towards sustainable agriculture - Swati Mangla; Yogesh K. Ahlawat; Gaurav Pathak; Nisha Sharma; Maryam Samani; Veer Bhan; Jemaa Essemine; Yashirdisai Sampasivam; Navjot Singh Brar; Anurag Malik; Vikas Ramteke; Shivali Gupta; et al. (Functional & Integrative Genomics, 2025)

Do microplastics play a role in the pathogenesis of neurodegenerative diseases? Shared pathophysiological pathways for Alzheimer’s and Parkinson’s disease - Alexander Chi Wang Siu; Keshav Raj Paudel; Gurjeet Singh; Gaurav Gupta; Sachin Kumar Singh; Dinesh Kumar Chellappan; Gabriele De Rubis; Suhrud Pathak; Brian Gregory George Oliver; Kamal Dua; Muralikrishnan Dhanasekaran (Molecular and Cellular Biochemistry, 2025)
The widespread presence of microplastics (MPs) in the environment has raised significant concerns about their potential impact on human health. As of 2023, the Ocean Conservancy estimates that adults may ingest up to 121,000 MPs annually. While the majority of these particles are cleared from the body, a small fraction can persist, as MPs are non-biodegradable and resist breakdown, posing long-term health risks that remain poorly understood. This review explores the emerging link between MP exposure and the development of neurodegenerative diseases, particularly Alzheimer’s disease (AD) and Parkinson’s disease [1]. MPs appear capable of triggering neurotoxic pathways, including activation of resident immune cells in the brain, oxidative stress, blood–brain barrier (BBB) disruption, mitochondrial dysfunction, and neuronal damage, which may contribute to neuroinflammation and disease progression. Specifically, six MP-related mechanistic pathways associated with AD were identified: BBB disruption, chronic inflammation, oxidative stress and ROS generation, mitochondrial dysfunction, impaired autophagy and proteostasis, and epigenetic alterations. Similarly, six pathways were implicated in PD: BBB disruption, oxidative stress in dopaminergic neurons, mitochondrial dysfunction, microglial-driven neuroinflammation, α-synuclein aggregation, and gut–brain axis [2] disruption. Ultimately, our findings underscore the urgent need for further research into the neurological consequences of chronic MP exposure in humans and highlight the importance of strengthening global policies to curb plastic pollution and mitigate its long-term health risks.

Premature mortality risk and associated economic loss assessment due to PM2.5 exposure in Delhi, India during 2015–2019 - Amrendra Kumar Singh; Ashutosh Kumar Pathak; Gaurav Saini (Air Quality, Atmosphere & Health, 2024)

Can graphene-based composites and membranes solve current water purification challenges - a comprehensive review - Chetna Tewari; Gaurav Tatrari; Sumit Kumar; Mayank Pathak; Kundan Singh Rawat; Young Nam Kim; Biswajit Saha; Yong Chae Jung; Prithu Mukhopadhyay; Nanda Gopal Sahoo (Desalination, 2023)

Correction: The effects on performance and emission characteristics of DI engine fuelled with CeO2 nanoparticles addition in diesel/tyre pyrolysis oil blends - Upendra Rajak; Prerana Nashine; Prem Kumar Chaurasiya; Tikendra Nath Verma; Abhishek Dasore; Kamal Kishore Pathak; Gaurav Dwivedi; Anoop Kumar Shukla; Gaurav Saini (Environment, Development and Sustainability, 2022)

The effects on performance and emission characteristics of DI engine fuelled with CeO2 nanoparticles addition in diesel/tyre pyrolysis oil blends - Upendra Rajak; Prerana Nashine; Prem Kumar Chaurasiya; Tikendra Nath Verma; Abhishek Dasore; Kamal Kishore Pathak; Gauav Dwivedi; Anoop Kumar Shukla; Gaurav Saini (Environment, Development and Sustainability, 2022)

Long-term spatiotemporal trends of temperature associated with sugarcane in west India - RN Singh; Sonam Sah; Bappa Das; Gaurav Chaturvedi; Mahesh Kumar; Jagadish Rane; Himanshu Pathak (Arabian Journal of Geosciences, 2021)

Monitoring Quality of Biotherapeutic Products Using Multivariate Data Analysis - Anurag S. Rathore; Mili Pathak; Renu Jain; Gaurav Pratap Singh Jadaun (The AAPS Journal, 2016)

Calcium triggers protein kinases-induced signal transduction for augmenting the thermotolerance of developing wheat (Triticum aestivum) grain under the heat stress - Suneha Goswami; Ranjeet R. Kumar; Sushil K. Sharma; Yugal K. Kala; Khushboo Singh; Richa Gupta; Gaurav Dhavan; Gyanendra K. Rai; Gyanendra P. Singh; Himanshu Pathak; Raj D. Rai (Journal of Plant Biochemistry and Biotechnology, 2015)

Corticosteroids affect nitric oxide generation, total free radicals production, and nitric oxide synthase activity in monocytes of asthmatic patients - Krishan Lal Khanduja; Gaurav Kaushik; Suchit Khanduja; Chander Mohan Pathak; Judy Laldinpuii; Degambar Behera (Molecular and Cellular Biochemistry, 2011)